2020
DOI: 10.1155/2020/9356738
|View full text |Cite
|
Sign up to set email alerts
|

Radixin Relocalization and Nonmuscle α-Actinin Expression Are Features of Remodeling Cardiomyocytes in Adult Patients with Dilated Cardiomyopathy

Abstract: Background. Pediatric patients show an impressive capacity of cardiac regeneration. In contrast, severely deteriorated adult hearts do usually not recover. Since cardiac remodeling—involving the expression of fetal genes—is regarded as an adaptation to stress, we compared hearts of adult patients suffering from dilated cardiomyopathy (DCM) with remodeling of cultured neonatal (NRC) as well as adult (ARC) rat cardiomyocytes and the developing postnatal myocardium. Methods. NRC and ARC were stimulated with serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Threonine residue 308 (Thr308) in the Akt kinase was strongly phosphorylated, although little activation of serine 473 was observed. ERM proteins (ezrin, radixin and moesin) are a further indicator of cellular activation [ 10 , 11 ]. They stabilize the membrane and the actin cytoskeleton and are regarded as linker proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Threonine residue 308 (Thr308) in the Akt kinase was strongly phosphorylated, although little activation of serine 473 was observed. ERM proteins (ezrin, radixin and moesin) are a further indicator of cellular activation [ 10 , 11 ]. They stabilize the membrane and the actin cytoskeleton and are regarded as linker proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Morphogens also induced the reexpression of α-actinin-1 and β-actin, but both proteins were barely detectable in serum-treated groups ( Figure 1 A,B). α-Actinin-1 appears to be a new marker of cardiac remodeling since it is reexpressed in cardiomyocytes of patients with dilated cardiomyopathy, aortic stenosis, and myocardial infarction, as well as in mice with myocarditis, dilated cardiomyopathy, and infarction [ 11 , 12 , 13 , 16 , 25 , 26 , 27 ]. Skeletal actin is present in adult rat cardiomyocytes and was downregulated by serum at day 10 but recovered thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…Primary cultures of adult cardiomyocytes offer an ideal toolbox to analyze the general behavior of stress-activated myocytes in the diseased myocardium since they transfer their genetic, epigenetic, and proteomic statuses into the culture dish [ 25 , 27 ]. By this a number of novel biomarkers of cardiac remodeling and failure can be determined and basic principles of cardiac disease development analyzed [ 24 , 25 , 27 ]. Here, we wanted to know whether structural and MAPK remodeling can be observed in cardiomyocytes of patients with dilated cardiomyopathy (DCM).…”
Section: Resultsmentioning
confidence: 99%
“…The GO and pathway enrichment analysis was of great importance for interpreting the molecular mechanisms of the key cellular activities in PCOS. RPS5 [ 37 ], RBM3 [ 38 ], BAK1 [ 39 ], NDUFC2 [ 40 ], NDUFS4 [ 41 ], NDUFS5 [ 42 ], UQCRFS1 [ 43 ], COX6B1 [ 44 ], NDUFA13 [ 45 ], PRMT1 [ 46 ], RDX (radixin) [ 47 ], EPHB4 [ 48 ], SYNE2 [ 49 ], DNAH5 [ 50 ], NEDD4L [ 51 ], PDE4B [ 52 ] and CTNND1 [ 53 ] plays a critical role in the process of cardiovascular disease, but these genes might be linked with development of PCOS. Ostergaard et al [ 54 ], Zi et al [ 55 ], Kunej et al [ 56 ], Van der Schueren et al [ 57 ], Jin et al [ 58 ], Emdad et al [ 59 ], Liu et al [ 60 ], Scherag et al [ 61 ], Shi and Long [ 62 ], Sharma et al [ 63 ], Parente et al [ 64 ], Saint-Laurent et al [ 65 ] and Lee [ 66 ] demonstrated that over expression of COA3, PHB (prohibitin), UQCRC1, COX4I1, IFI27, MTDH (metadherin), S100A16, SDCCAG8, GLI2, NTN1, NLGN2, FGFR3 and PTPRN2 could cause obesity, but these genes might be involved in progression of PCOS.…”
Section: Discussionmentioning
confidence: 99%